1999
DOI: 10.2166/wst.1999.0074
|View full text |Cite
|
Sign up to set email alerts
|

The impact of agricultural pollutants in six drinking water reservoirs

Abstract: Water is supplied in the Greater Istanbul Metropolitan Area from the surface water of six main reservoirs. The present land use in the catchment areas of the reservoirs indicates that the area devoted to agricultural activities and to forests and meadows varies between 73 and 97% and that only a minor percentage, 1-26%, is devoted to settlements and industries. In contrast to the land use profile, the current environmental evaluation of the catchment areas reveals that point sources dominate over diffuse sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…To detect the major causes of surface water pollution, the Nilüfer stream basin was divided into 4 sub-basins and the border of sub-basins were detected by using topographical maps scaled 1/100 000. Characteristics of land cover in subbasins were determined with the help of Geographic Information Systems (GIS) : , Tanık, A. et al, 1999 as shown in Figure 2 and pollution loads were estimated from diverse sources. The flows of each subsystem were then further divided by point diffuse pollution loading assessments.…”
Section: Procedures For Materials Flow Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To detect the major causes of surface water pollution, the Nilüfer stream basin was divided into 4 sub-basins and the border of sub-basins were detected by using topographical maps scaled 1/100 000. Characteristics of land cover in subbasins were determined with the help of Geographic Information Systems (GIS) : , Tanık, A. et al, 1999 as shown in Figure 2 and pollution loads were estimated from diverse sources. The flows of each subsystem were then further divided by point diffuse pollution loading assessments.…”
Section: Procedures For Materials Flow Analysismentioning
confidence: 99%
“…Pollution load coming from diffuse sources was estimated by multiplying export coefficients with the area of land use shown in Table I. Phosphorus and nitrogen export coefficients for land use are selected from the literature on similar basins within the Marmara region (Öktem, 1996;Tanık et al, 1999). Due to constraints in data availability in atmospheric measurements, the annual phosphorus and nitrogen loads could not be calculated.…”
Section: Procedures For Materials Flow Analysismentioning
confidence: 99%
“…Sediments can accumulate behind dams, which results in the siltation of water reservoirs (Downing et al, 2008;Thothong et al, 2011). Suspended organic matter also contributes to water quality degradation (Tanik et al, 1999) and plays a major role in nutrient biogeochemical cycles (Quinton et al, 2010). It also constitutes a potential vector for various contaminants such as metals, polycyclic aromatic hydrocarbons or faecal bacteria (Ribolzi et al, 2010;Gateuille et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Vegetation and agriculture) TN and TP loads = Land utilization area * Transport (1) coefficients The TN and TP loads resulting from small settlements within the catchment basin of MKP Stream with a population below 2000 were calculated by multiplying daily pollution load unit coefficients per person [20,22] by population values [23]. The TN and TP loads stemming from small settlements were given by the Equation (2) below:…”
Section: Calculation Of Pollution Loadsmentioning
confidence: 99%